Morphological and structural analyses in carbonated magnesium-aluminum hydrotalcites co-substituted with iron iii - Kawahara, Creuza Kimito Caceres; Barbosa, Graciele Vieira; de Sá, Igor Silva; Gonçalves, Sabrina Vitor; Amoresi, Rafael Aparecido Ciola [UNESP]; Zaghete, Maria Aparecida [UNESP]; da Silva, Margarete Soares; Cavalheiro, Alberto Adriano (Trans Tech Publications, 2018)
Magnesium-aluminum hydrotalcites can be co-substituted with others trivalent cations, such as iron III in aluminum site, which can be a promising way to modify the properties of that synthetic adsorptive material. In the present work, hydrotalcite containing 5 mol% iron III in co-substitution to the aluminum was prepared by precipitation process and compared with no co-substituted sample along the temperature of calcination at 100 and 500 ºC for 4 hours. The calcined samples were characterized by simultaneous TG/DTA, X-ray Diffraction and nitrogen adsorption-desorption techniques. The iron (III) insertion showed positive results in order to provide more stable structure against high temperatures of calcination, which was observed by lesser structural decomposition of rhombohedral hydrotalcite and a more mesoporous structure.
Keywords: Hydrotalcite; Porosity; Precipitation Hydroxides; Thermal Analysis